Influenza outbreaks with a focus on closed psychiatric units: A review article - Pradeep Kumar Mada; Daniel Alexander Saldaña Koppel; Gabriel Castano; Matthew E Malus; Sharon Adley NP; Denise Taylor RN; Mohammad Alam (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2018)
2018 is a year to remember as we passed 100 years from the most catastrophic event in recorded history: the 1918 influenza pandemic. After that, we encountered three more influenza pandemics in 1957, 1968 and 2009. In 2018, Influenza season has been worse than recent previous seasons. Influenza activity in this year is comparable to 2009 H1N1 pandemic taking a terrible toll. Influenza, an acute respiratory illness caused by different strains of influenza A or B virus that occurs in outbreaks and epidemics worldwide. Psychiatric units represent a unique challenge for influenza outbreaks because they are closed units, and hygienic measures are harder to implement due to patient mental conditions. Early diagnosis and timely interventions are essential to decrease the burden of the disease. As a general recommendation, all persons older than six months without a contraindication should receive annual influenza vaccination, especially populations at a higher risk of medical complications.